ANALISIS PEMBELAJARAN AL-QUR’AN DAN HADIS BERBASIS KURIKULUM MERDEKA DI MADRASAH IBTIDAIYAH: IMPLEMENTASI PEMBELAJARAN ABAD 21: IMPLEMENTASI PEMBELAJARAN ABAD 21 - Raden Syaifuddin; Sholikha, Risma Amaliatus (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
Islamic schools (madrasas) that have Islamic values support the development of students as God's creations in this world. The application of an Islamic competency-based approach to the school curriculum (madrasah) can be done through subjects taught at school. The learning of Al-Qur'an and Hadith is vital for nurturing informed and ethical members of the Muslim community. By employing effective teaching methods and addressing challenges, educators can enhance the understanding and application of these foundational texts in students' lives subjects based on the independent curriculum in Islamic elementary schools (Madrasah Ibtidaiyah). The research uses qualitative methods using a lot of library material. The results of this research are that the independent curriculum and the sophistication of 21st century technology is a very good collaboration in learning the Al-Qur'an and Hadith for students, through talent, interest in implementing or exploring learning that is more flexible and adapts students to learning. Learning the Al-Qur'an and Hadith based on the independent curriculum has a significant impact on learning because students have more freedom in learning even though they have to remain under teacher supervision.